PERAN PENDAMPINGAN PSIKOLOGI FORENSIK DALAM MENDUKUNG SAKSI KEKERASAN SEKSUAL - Anisa Ayu Febrianti; Aisha Malika, Bella Aisyah Dinah, Benita Azlia Fauziyah, Ratu Dwinov Putri, Syafina Wanilawati, Tugi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
Sexual violence is a violation of human rights and can occur in various forms, ranging from sexual harassment to sexual coercion without the victim's consent. A deep understanding of sexual violence and its impacts is crucial for creating a safe and supportive environment for the victims. Psychological support is an important aspect in the recovery process of witnessesand victims of sexual violence. This research aims to analyze the role of forensic psychological support for sexual violence witnesses. The study employs a literature review method, utilizing various sources such as Google Scholar and educational books that focus oncase studies of the role of forensic psychological support in assisting sexual violence witnesses. The role of psychological support provided to witnesses includes Rehabilitation, Eye Movement Desensitization and Reprocessing (EMDR), Psychological First Aid (PFA), and Therapy Support Groups. This support helps victims understand and process the trauma they have experienced and develop healthy coping mechanisms. Providing appropriate psychological support to help victims manage trauma includes several important steps, with these strategies enabling victims to develop effective coping mechanisms and enhance their recovery journey